2007
DOI: 10.1021/es071492j
|View full text |Cite
|
Sign up to set email alerts
|

Body Loadings and Health Risk Assessment of Polychlorinated Dibenzo-p-dioxins and Dibenzofurans at an Intensive Electronic Waste Recycling Site in China

Abstract: This study is one of the very few investigating the dioxin body burden of a group of child-bearing-aged women at an electronic waste (e-waste) recycling site (Taizhou, Zhejiang Province) (24 ( 2.83 years of age, 40% were primiparae) and a reference site (Lin'an city, Zhejiang Province, about 245 km away from Taizhou) (24 ( 2.35 years of age, 100% were primiparae) in China. Five sets of samples (each set consisted of human milk, placenta, and hair) were collected from each site. Body burdens of people from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 188 publications
(119 citation statements)
references
References 53 publications
4
106
2
1
Order By: Relevance
“…The highest values of these compounds in hair were found by the present study. Because hair can reflect the body's integral exposure to POPs from endogenous and exogenous sources (2,39), the results showed that the E-waste dismantling workers in the LQ area heavily accumulated PCDD/ Fs, PBDEs, and PCBs in their bodies.…”
Section: Resultsmentioning
confidence: 99%
“…The highest values of these compounds in hair were found by the present study. Because hair can reflect the body's integral exposure to POPs from endogenous and exogenous sources (2,39), the results showed that the E-waste dismantling workers in the LQ area heavily accumulated PCDD/ Fs, PBDEs, and PCBs in their bodies.…”
Section: Resultsmentioning
confidence: 99%
“…E-waste recycling operations have been ongoing for approximately 30 years in this area. According to the Economic and Trade Commission of Taizhou in 2005, more than 2 million metric tons of e-waste were processed in Taizhou annually, and 40,000 people were employed in the e-waste recycling industry (Chan et al, 2007). Wenling city is one of the major cities involved in e-waste recycling close to the city centre in Taizhou area with a total area of 836 km 2 and a population of 1.4 million.…”
Section: Sample Areamentioning
confidence: 99%
“…S1a and b). The profiles for GY and TZ samples closely resembled those for the GY riverbank soil and TZ human hair (Chan et al, 2007), indicating that there were emission sources at the sampling sites . The riverbank soil collected in Leung et al's (2007) study and the fish collected in the present study were from the same rivers in GY.…”
Section: Congener Concentrations and Homologue Profilesmentioning
confidence: 65%
“…Both GY and TZ are the 2 major e-waste processing sites in China, where the former is located in Guangdong Province, southern China while the latter is in Zhejiang Province, eastern China (Fig. 1, Chan et al, 2007). The reference site chosen was LN, which is situated inland in Zhejiang Province, northern Hangzhou, about 245 km away from TZ and has no history of e-waste recycling activities.…”
Section: Sampling Sitesmentioning
confidence: 99%
See 1 more Smart Citation